Socioeconomic Disparities in Medical Provider Visits among Medicare Managed Care Enrollees - Jeannette Rogowski; Vicki A. Freedman; Steve L. Wickstrom; John Adams; José J. Escarce (SAGE Publishing, 2008)
This study examined socioeconomic disparities in medical provider visits for elderly people enrolled in two Medicare managed care plans. Controlling for health and demographic differences, elderly people of lower income had fewer primary care visits and those with lower education had fewer specialist visits. The number of emergency room visits was not significantly related to socioeconomic status (SES). People of low SES reported having more financial barriers to receiving care and greater difficulties navigating the managed care system than people of high SES. Further, elderly people of low SES had different degrees of belief in the efficacy of the medical system and of lifetime experiences with a usual source of medical care prior to Medicare, both of which were associated with differential use of medical providers.